Contrast Media Administration in Coronary Computed Tomography Angiography – A Systematic Review - Mihl, Casper; Maas, Monique; Turek, Jakub; Seehofnerova, Anna; Leijenaar, Ralph T.H.; Kok, Madeleine; Lobbes, Marc B.I.; Wildberger, Joachim E.; Das, Marco (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Background Various different injection parameters influence enhancement of the coronary arteries. There is no consensus in the literature regarding the optimal contrast media (CM) injection protocol. The aim of this study is to provide an update on the effect of different CM injection parameters on the coronary attenuation in coronary computed tomographic angiography (CCTA).Method Studies published between January 2001 and May 2014 identified by Pubmed, Embase and MEDLINE were evaluated. Using predefined inclusion criteria and a data extraction form, the content of each eligible study was assessed. Initially, 2551 potential studies were identified. After applying our criteria, 36 studies were found to be eligible. Studies were systematically assessed for quality based on the validated Quality Assessment of Diagnostic Accuracy Studies (QUADAS)-II checklist.Results Extracted data proved to be heterogeneous and often incomplete. The injection protocol and outcome of the included publications were very diverse and results are difficult to compare. Based on the extracted data, it remains unclear which of the injection parameters is the most important determinant for adequate attenuation. It is likely that one parameter which combines multiple parameters (e. g. IDR) will be the most suitable determinant of coronary attenuation in CCTA protocols.Conclusion Research should be directed towards determining the influence of different injection parameters and defining individualized optimal IDRs tailored to patient-related factors (ideally in large randomized trials).Key points Citation Format
Keywords: cardiac; contrast agents; technical aspects; CT angiography